Electrodeposition of kesterite thin films for photovoltaic applications: Quo vadis? (Phys. Status Solidi A 1∕2015). Issue 1 (January 2015) - Colombara, D.; Crossay, A.; Vauche, L.; Jaime, S.; Arasimowicz, M.; Grand, P.‐P.; Dale, P. J.
<x xml:space="preserve">Abstract</x> Due to the Earth‐abundance of the metallic constituents copper, zinc and tin, Cu2ZnSn(S, Se)4 kesterite‐based solar cells are being intensively studied as a promising thin film photovoltaic technology potentially capable of reaching the terawatt‐scale electricity supply in the 21st century. In the Review Article by Colombara et al. (pp. 88–102), the focus is on electrodeposition (ED) as a means to obtain kesterite‐based solar cells. ED is a well‐established manufacturing technology employed from the automotive to microelectronic industry. It allows fabricating largearea coatings with high throughput, low capital expenditure and low material usage. Still, an efficiency gap exists between the world record and the best state‐of‐the‐art ED‐based kesterite solar cells. There are three main kesterite‐ED strategies: (i) stacked metallic elemental layers, (ii) metal alloys, and (iii) quaternary compound. In this review the strengths and opportunities offered, as well as the weaknesses and threats posed by each of these approaches are critically assessed with respect to their potential to achieve the highest solar cell efficiencies, with a particular attention to the Academia‐to‐Industry knowledge transfer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>